Undergraduate Students’ Difficulties in Writing Descriptive Paragraph - Marhatus Sholeha; Imam Ghozali; Moh. Arif Mahbub (English Education Department, Faculty of Teacher Training and Education, Islamic University of Jember, 2017)
The aim of this study is to identify the difficulties of linguistic aspects in writing descriptive paragraph experienced by undergraduate students at English Education Program of UIJ. It used descriptive qualitative research method. The subjects were 20 students of English Education Program at second semester. They were instructed to write 100 – 150 words about descriptive paragraph entitled “A Description of My Village”. After investigating students’ writing product, the result of the research revealed that the students faced some difficulties in linguistic aspects. The most common difficulties of linguistic aspects made by the students were vocabulary problems (21,5%). Secondly, a cognitive problem was capitalization (20,5%), then fragments (16%) as a sentence structure problem, punctuation (14%) as a cognitive problem, spelling (6%) as a cognitive problem, preposition (5,5%) as a grammatical problem, word order and SVA (5%) as sentence structure problems. In addition, the follow-up interview supported these findings by indicating that most students was still assisted by looking up the dictionary in determining appropriate vocabularies. It was suggested that provide specific descriptions of linguistic aspects in writing skill be designed by the writing’s lecturers to improve students’ writing.